The Soviet biological weapons program a history - Leitenberg, Milton (Harvard University Press, 2012)
This is the first attempt to understand the broad scope of the USSR's offensive biological weapons research from its inception in the 1920s. Gorbachev tried to end the program, but the US and UK never obtained clear evidence he succeeded, raising the question whether the means for waging biological warfare could be revived in Russia in the future.